1971
DOI: 10.1213/00000539-197103000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Severe Reaction to Accidental Subcutaneous Administration of Large Doses of Epinephrine

Abstract: CCIDENTAL drug overdosage, a 1 ways A troublesome, is perhaps never so dramatic as when the drug is epinephrine. The case report and discussion to follow are concerned with the accidental subcutaneous injection of about 10 ml. of a 1:2OOO solution of epinephrine (5 mg.) and its degradation and urinary excretion. REPORT OF A CASEA 41-year-old obese and mentally-retarded woman with a basal-cell nevus syndrome was admitted to the University of Virginia Hospital for excision of numerous basal-cell carcinomas, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Carter hypothesized that exogenous epinephrine may trigger endogenous catecholamines by demonstrating that excreted epinephrine metabolites doubled that expected from a 5‐mg subcutaneous injection. 6 Epinephrine is a potent adrenergic stimulator with sensitive beta‐adrenergic receptors that cause increased heart rate, cardiac output, and myocardial oxygen consumption. Overstimulation may lead to cardiac arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carter hypothesized that exogenous epinephrine may trigger endogenous catecholamines by demonstrating that excreted epinephrine metabolites doubled that expected from a 5‐mg subcutaneous injection. 6 Epinephrine is a potent adrenergic stimulator with sensitive beta‐adrenergic receptors that cause increased heart rate, cardiac output, and myocardial oxygen consumption. Overstimulation may lead to cardiac arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with the beta‐adrenergic effects, hypertension develops. 6 Reflex bradycardia can develop by stimulation of carotid baroreceptors by severe hypertension. 7 Pulmonary edema develops secondary to epinephrine causing increased peripheral vascular resistance and tachycardia leading to decreased diastolic filling time, cardiac failure, and subsequent increased pulmonary circulation pressure.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, there have been reports on epinephrine administration resulting in severe, and sometimes fatal, CV complications 1113. Epinephrine increases cardiac output through action on the β 1 -adrenergic receptors in the heart 2.…”
Section: Complicationsmentioning
confidence: 99%
“…Many parents have reservations about potentially using an EAI to administer epinephrine to their children due to concerns over injury, incorrect use, and poor outcomes 10. Prevalent safety concerns regarding the use of EAIs include cardiovascular (CV) complications,1113 accidental injections,1416 laceration injuries,17,18 and the use of expired EAIs 19. The present literature review provides an overview of anaphylaxis and discusses the safety concerns, highlighting the recent developments on their frequency, severity, and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the possibility that epinephrine caused hypersensitization in the body cannot be ruled out. Carter et al 10) measured the discharged epinephrine and the metabolites after an epinephrine injection and reported that the detected amount was 2 times more than the expected value, which can lead to cardiovascular crisis, such as arrhythmia and cardiac arrest. They mentioned the possibility of endogenous epinephrine hypersensitization by the externally injected epinephrine.…”
Section: +mentioning
confidence: 99%